Khidmat Mahasiswi KKN STIBA Makassar melalui Kegiatan Keagamaan pada Masyarakat Kelurahan Biring Romang Kecamatan Manggala Kota Makassar - Zulfiah Sam; Ahmad Syaripudin (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2022)
The purpose of the Field Work Lecture (KKN) Batch V of STIBA Makassar students is to increase Islamic knowledge and religious awareness in the people of the Biring Romang Village, Manggala District, Makassar. This KKN is a form of community service as one of the pillars of the Tridarma of Higher Education. The method of implementing the community service program begins with mapping community problems and needs using SOAR Analysis. After the analysis is carried out, a work program is prepared according to the needs of the community. The work program that was successfully carried out at Biring Romang was a solemn form of KKN students for the people of the Biring Romang Village, including fostering religious activities such as teaching the Quran for adults or DIROSA and children trough teaching TPA, Daurah memorizing the Quran, Taklim Muslimah, Daurah Ta’rif, Teaching al Quran in several schools, Traaining on Organizing Bodies, Social Service, Ghatering, Friday sharing and Ramadhan sharing. The results of this activity is that the enthusiasm and enthusiasm of the community, especially women and children, is visible in participating in the activity, especially the Dirosa and TPA activities which formed several halaqahs at several points is Biring Romang Village and their very big hope that these activities will always be continues even though the KKN period has ended. And all of these programs are running well and have shown initial results in accordance with the aims of the KKN that have been proclaimed.